A living WHO guideline on drugs to prevent covid-19. (1st March 2021) - Lamontagne, François; Agoritsas, Thomas; Siemieniuk, Reed; Rochwerg, Bram; Bartoszko, Jessica; Askie, Lisa; Macdonald, Helen; Amin, Wagdy; Bausch, Frederique Jacquerioz; Burhan, Erlina; Cecconi, Maurizio; Chanda, Duncan; et al.
Abstract: Clinical question: What is the role of drugs in preventing covid-19? Why does this matter?: There is widespread interest in whether drug interventions can be used for the prevention of covid-19, but there is uncertainty about which drugs, if any, are effective. The first version of this living guideline focuses on the evidence for hydroxychloroquine. Subsequent updates will cover other drugs being investigated for their role in the prevention of covid-19. Recommendation: The guideline development panel made a strong recommendation against the use of hydroxychloroquine for individuals who do not have covid-19 (high certainty). How this guideline was created: This living guideline is from the World Health Organization (WHO) and provides up to date covid-19 guidance to inform policy and practice worldwide. Magic Evidence Ecosystem Foundation (MAGIC) provided methodological support. A living systematic review with network analysis informed the recommendations. An international guideline development panel of content experts, clinicians, patients, an ethicist and methodologists produced recommendations following standards for trustworthy guideline development using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Understanding the new recommendation: The linked systematic review and network meta-analysis (6 trials and 6059 participants) found that hydroxychloroquine had a small or no effect on mortality and admission to hospital (high certainty evidence). There was a small or no effect on laboratory confirmed SARS-CoV-2 infection (moderate certainty evidence) but probably increased adverse events leading to discontinuation (moderate certainty evidence). The panel judged that almost all people would not consider this drug worthwhile. In addition, the panel decided that contextual factors such as resources, feasibility, acceptability, and equity for countries and healthcare systems were unlikely to alter the recommendation. The panel considers that this drug is no longer a research priority and that resources should rather be oriented to evaluate other more promising drugs to prevent covid-19. Updates: This is a living guideline. New recommendations will be published in this article and signposted by update notices to this guideline. Readers note: This is the first version of the living guideline for drugs to prevent covid-19. It complements the WHO living guideline on drugs to treat covid-19. When citing this article, please consider adding the update number and date of access for clarity.